D+D fusion reactions in 1018 W/cm2 intensity and repetitive laser-plasma interactions. (13th December 2017) - Giulietti, D.; Boutoux, G.; Aïche, M.; Andrianaki, G.; Batani, D.; Burgy, F.; Cipriani, M.; Consoli, F.; De Angelis, R.; Ducret, J. E.; Hulin, S.; Jardin, A.; et al.
Abstract: We studied D + D fusion reactions at the CELIA/ECLIPSE laser facility. These reactions were triggered by focusing the ECLIPSE laser (up to 100 mJ on target, pulse duration of 40 fs and focal spot of FWHM) on a solid C2 D4 target. By detecting the 2.5 MeV neutrons, produced in the D + D fusion reaction, using C6 D6 scintillators in a time-of-flight experimental set-up, we measured a rate of a few hundred fusions per shot. At the same time, we detected also energetic ions (up to a few 100 keV) using time-of-flight diamond detectors. The experimental set-up will be presented and the results discussed and compared with dedicated simulations.